Students' Challenges of Blended Learning Model in Higher Education - Lanlan Muhria; Nana Supriatna; Nunu Nurfirdaus (CV. Tripe Konsultan, 2023)
Blended learning is a general term for a method that combines the benefits of classroom learning with online learning. However, the combination of online and face-to-face educational components has caused problems over time. Some studies highlight the general limitations of the blended learning education model, but there is no clear insight into the challenges that exist in the blended learning online component. A systematic literature search was performed to identify obstacles to the online components of blended learning from a student's perspective. The biggest challenges students face are self-regulatory issues and the difficulty of learning technology. This study highlights the need for further research to address the problem of student blended learning.